Sustainable development goals in the Apurimac region - Rivas-Huaman, Rolly (2022)
This informative article shows the reality of the Apurímac region regarding the Sustainable Development Goals from objective n° 10 to objective n° 17. The first objective is to show in a descriptive way the statistical data on the current reality of the Apurímac region in the implementation of the SDGs. The second objective is to disseminate the SDGs and sensitize the national and regional population about its benefits. A third objective is to promote among local and national authorities the importance of implementing the SDGs in public policies in the Apurímac region, describing, in turn, the results achieved until the year 2021. The methodology used was the documentary review, which consisted of review the Institutional Strategic Plan [PEI] of the Regional Government of Apurímac to verify the percentage of SDG implementation within its strategic objectives, considering its execution and compliance, among other documents. It was found that, although there are sustainable development objectives that are being implemented within the policies of the regional government of Apurímac, other SDGs still need to be included.